Development of mobile structures to protect railway tracks from rockfall (Международный научный журнал «Инженер», 2026)
The article develops the design of a mobile protective structure depending on the trajectory of the stonesto protect the railway track from stones. The use of mobile protective structures chosen to protect therailway track from external influences is justified, taking into account the trajectory, flight range, heightof falling stones from the mountain and the value of impact dynamic forces arising from a collision withthe structure. Also, various designs of mobile protective structures are presented, while taking intoaccount the possibility of moving structures from an inactive rockfall site to an active one and obtaininglower costs from an economic point of view.